スピッツベルゲントウ コングスフィヨルド カイヨウ チョウサ カイヨウ コウゾウ ノ カンソク 1991-1993 ネン - 牛尾, 収輝; ウシオ, シュウキ; 伊藤, 一; イトウ, ハジメ; 小野, 延雄; オノ, ノブオ; Ushio, Shuki; Ito, Hajime; Ono, Nobuo (1995)
P(論文) 1991年から1993年の間, 5回にわたってスピッツベルゲン島コングスフィヨルドの海洋調査を実施した。その内, 海洋構造を把握するために行った水温・塩分分布観測の概要について報告する。観測結果より, 周辺陸域からの融雪水の流入や外洋(フラム海峡)起源の高密度水の滞留が海洋構造の特徴形成に寄与していることが示唆された。 Oceanographic surveys were carried out five times in the Kongsfjorden, Spitsbergen during 1991-1993. This report describes an outline of in situ observations of the water structure, temperature and salinity profiles, in the fjord. Based on the preliminary results, it is suggested that the surface layer is influenced by the fresh water inflow from melting of the surrounding snow pack or glaciers, and that the deep water mass is gradually changed in quality by the dense water intrusion from the open ocean, Fram Strait. departmental bulletin paper